2017
DOI: 10.7309/jmtm.6.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perception on the Use of QR Code Versus Traditional Pen-and-Paper as an Attendance Record Tool in Medical School

Abstract: Background: Student attendance at teaching-learning sessions is traditionally registered using pen-and-paper. This method has many weaknesses: lost, hard to verify, attendance-by-proxy, late submission. The Quick-Response Code is a two-dimensional barcode that can be read with a QR reader on a smartphone that captures and instantly transmits information to a cloud storage. We describe the use of a QRC method to register medical students' attendance and assessed their perception of this method compared to PAP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Enabling geolocation and incorporating it as a crucial step in the scanning and submission process ensured that only in-class attendees submitted their attendance. This passes in agreement with Koh and his colleagues, who also mentioned the risk of fraud and proxy attendance from sharing or sending the QR code remotely to absentees [16].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Enabling geolocation and incorporating it as a crucial step in the scanning and submission process ensured that only in-class attendees submitted their attendance. This passes in agreement with Koh and his colleagues, who also mentioned the risk of fraud and proxy attendance from sharing or sending the QR code remotely to absentees [16].…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the findings of a different study conducted by David and his associates, which determined that QR code is a significantly more convenient method for both students and faculty that can benefit users who prioritize functionality, reliability, and maintainability when checking student attendance [15]. Additionally, compared to the traditional PAP approach, Koh and his colleagues deemed the QR code attendance record tool to be a safer, more favorable, and more convenient method for recording class attendance [16]. Moreover, another study by Molina demonstrated that employing QR codes for data access is not only timesaving and easy, but also environmentally friendly and cost-effective [17].…”
Section: Discussionsupporting
confidence: 83%
“…e IoT is a consequence of the ongoing evolution of IT. In the realm of the IoT, different kinds of factors can talk to each other and only need to share information needs through the IoT language technology [11,12], which has the following characteristics:…”
Section: Web Of Objects Skillsmentioning
confidence: 99%
“…Traditional paper leaflets are not future-proof and would require reprinting and have a further impact on the environment. These advantages are confluent with the current literature where the use of QR code smartphone technology were reported to improve knowledge, be more convenient, accurate, secure and environmentally friendly (Dixon et al, 2013;Uzun and Bilgin, 2016;Koh et al, 2017).…”
Section: Benefits Of Qr Codesmentioning
confidence: 78%